MONITORING OF PRODUCTION WASTE FROM THE SUINUCULTURA - Martinez, D. G.; Pinheiro, F. S.; Kitamura, D. S.; de Souza, S. N. M.; Feiden, A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Energy production from biomass can contribute significantly, as well as to reduce carbon emissions into the atmosphere and also minimize water contamination problem in the case of waste from livestock and municipal solid waste. Faced with this problem, this study aimed to, monitor the amount of waste produced by animals on the farm (L/day) , and also the production of biomass from farm ( m³ / day). Analyses were performed on Unit Colombari Granja, located in the municipality of San Miguel-PR, west of Paraná. Volume control was carried out by means of a volumetric measurement system, from water tank installed at the outlet of effluent from pig housing sheds. The data collection period was between the months of December 2011 and June 2012. During this period, the average volume of waste measured, corresponding to 82 pigs was approximately 723 liters of waste / day. It can be observed increased production waste in the months of December and January, reflecting higher consumption of water and in consequence the generation of waste